Nutritional limitations for beans on red prairie soil in Corumbá, Mato Grosso do Sul, Brazil - Dynia, José Flávio; Cunha, Noel Gomes da (Pesquisa Agropecuaria Brasileira, 2014)
Soil of the red prairie group, originated from limestone rocks bordering the Pantanal Matogrossense, was collected on savanna and on secondary forest vegetation areas near Corumbá, Mato Grosso do Sul, State, Brazil. Soil fertility test (using the missing element technique) performed in glasshouse evidenced strong defficiency of nitrogen, sulphur and phosphorus, and minor potassium defficiency for beans (Phaseolus vulgaris L.) on both soil samples.